Enhancement of Josephson phase diffusion by microwaves - Koval, Yury; Fistul, Mikhail; Ustinov, Alexey (Physical Review Letters, 2004)
The effect of microwave irradiation on the phase diffusion mesoscopic Josephson junctions was analyzed. Investigations show a smooth and incoherent enhancement of Josephson phase diffusion in small junctions by the microwaves. It was found that the voltage position Vtop of the peak increased with the power P of microwave irradiation and its current amplitude decreased with P. The results show the enhancement of incoherent superconducting current by the multiphoton absorption.
UnivIS-Import:2015-03-09:Pub.2004.nat.dphy.IAP.pephys.enhanc